An analytical disquisition on the nonlinear optical responses of carbon quantum dots engineered by diverse synthesis methodologies - Rashi Mahendra Patil; Akshay Raj R; Shyamal Mondal; Tejashree Bhave; Appala Venkata Ramana Murthy (Nano Trends)
Carbon quantum dots (CQDs) are highly promising nanomaterials known for their unique optical and electronic properties, which are crucial for applications in photonics, bioimaging, optoelectronics, etc. This study investigates the nonlinear optical (NLO) responses of CQDs synthesized via three different methods, namely, hydrothermal, microwave-assisted, and green synthesis. The three different synthesized CQDs have shown size-dependent optical and photoluminescence properties. The z-scan technique was employed for measuring the corresponding nonlinear absorption coefficient and nonlinear refractive index. Hydrothermal synthesis produced CQDs with strong NLO responses (χ(3) = 4.14 × 10–7 esu) due to high crystallinity and significant surface functionalization, whereas microwave-assisted synthesis resulted (χ(3) = 3.97 × 10–7 esu) in size-dependent NLO variability. Meanwhile, the green synthesis method, utilizing natural resources and organic precursors which replaced by chemical capping agents such as PEG, showed a moderate NLO response (χ(3) = 2.72 × 10–7 esu), influenced by diverse surface functionalities. This comparative analysis emphasizes the crucial role of synthesis methods in tailoring CQDs for specific NLO applications, providing insights to optimize their synthesis for enhanced performance in advanced optical technologies.